2021
DOI: 10.35502/jcswb.207
|View full text |Cite
|
Sign up to set email alerts
|

Alberta not criminally responsible project: Rates of persons found NCRMD and absolute discharges in Alberta following the Not Criminally Responsible Reform Act

Abstract: In 2014, then-Canadian Prime Minister Stephen Harper passed the Not Criminally Responsible Reform Act into law, which gave Canadian courts and Review Boards new powers to protect the public from particularly dangerous mentally ill offenders. The most controversial change to the law included the designation of the High-Risk Accused. Once designated by the courts as a High-Risk Accused, that individual is barred from leaving a forensic hospital except for urgent medical reasons. In this article, the authors asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…For instance, Olver and Sewall (2018) found that a measure of sexual violence risk incremented VRAG-R predictions, and that logistic regression could be used to model recidivism estimates incorporating treatment change information. This study findings also support the assertion of Canadian researchers elsewhere (Goossens et al, 2019;Grantham, 2014;Charette et al, 2015;Haag et al, 2021;Lacroix et al, 2017) that there is very little evidence that supports the idea that legislation change was needed to protect public safety (i.e., , given the lower levels of risk than general correctional samples and low rates of recidivism.…”
Section: Implications For Research and Practicesupporting
confidence: 83%
See 1 more Smart Citation
“…For instance, Olver and Sewall (2018) found that a measure of sexual violence risk incremented VRAG-R predictions, and that logistic regression could be used to model recidivism estimates incorporating treatment change information. This study findings also support the assertion of Canadian researchers elsewhere (Goossens et al, 2019;Grantham, 2014;Charette et al, 2015;Haag et al, 2021;Lacroix et al, 2017) that there is very little evidence that supports the idea that legislation change was needed to protect public safety (i.e., , given the lower levels of risk than general correctional samples and low rates of recidivism.…”
Section: Implications For Research and Practicesupporting
confidence: 83%
“…In response to increasing public pressure to ensure public safety and mental health, in 2014, Bill C-14, The Not Criminally Responsible Reform Act officially came into effect and made several amendments to the existing legislation, the most significant being the creation of a “high-risk accused” designation ( Bill C-14, 2014 ). There is skepticism over whether there is evidence to support the creation of the high-risk accused designation ( Goossens et al, 2019 ; Grantham, 2014 ; Haag et al, 2021 ; Lacroix et al, 2017 ). For instance, Goossens et al (2019) found the high-risk accused designation to be more closely linked to index offense severity as opposed to public safety risk.…”
Section: The Insanity Defense In Canada: Background and Contextmentioning
confidence: 99%
“…Most hearings took place prior to legislation that permitted more restrictive detention for individuals determined to be a “high‐risk accused” (Not Criminally Responsible Reform Act, 2014), so review board decisions might have changed since our data were collected. However, there is evidence that individuals meeting the high risk designation criteria were already being managed very conservatively (e.g., Goossens et al., 2019) and that the new designation has neither resulted in substantial changes to decision‐making nor significantly increased the duration of detention (e.g., Haag et al., 2021). During the COVID‐19 pandemic, review boards conducted hearings online but followed their normal mandate (e.g., Schneider, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and clinical characteristics of the sample were comparable to other Canadian NCR samples (Crocker, Nicholls, Seto, Charette, et al, 2015) and reported in Table 1. The study sample did not include any HRA individuals as the designation has not been used in Alberta since its inception in 2014 (Haag et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In a shift away from social rehabilitation in 2014, Bill C-14 attempted to (a) increase the emphasis on public safety needs behind dispositions, (b) increase the rights and involvement of victims, and (c) create a high-risk accused (HRA) designation to restrict transitions through the forensic system (Not Criminally Responsible Reform Act, 2014). Studies suggest that Bill C-14 has delayed social rehabilitation without benefit to public safety (Goossens et al, 2019; Grantham, 2014; Haag et al, 2021).…”
Section: Legislative Backgroundmentioning
confidence: 99%